A new species of Cephalocereus (Cactaceae) from southern Mexico - Arias, Salvador; Tapia, Héctor J.; Guzmán, Ulises (Phytotaxa, 2019)
Cephalocereus parvispinussp. nov. (Cactaceae) from the Mixtecan region (Oaxaca state, Mexico) is described and illustrated. The morphological and molecular evidence support its recognition as a distinct species within the genus Cephalocereus. The new species is characterized by arborescent habit up to 8 m in height, acrotonic branching, stems with 15−23 ribs; flowers 3.5−4 cm long, pericarpel and receptacular tube without podaria nor spines; fruit 1.7−2.2 cm long, dark red, with white flesh; seeds ca. 1.4 ×0.6 mm, dark brown, with a rugose micro-relief. The phylogenetic analysis usingseven cpDNA markers,shows that C. parvispinusis the sister species of C. polylophusand C. euphorbioides.